Patronin/Shot Cortical Foci Assemble the Noncentrosomal Microtubule Array that Specifies the Drosophila Anterior-Posterior Axis. - Nashchekin, D.; Fernandes, A.R.; St Johnston, D. (Developmental Cell, 2016)
Noncentrosomal microtubules play an important role in polarizing differentiated cells, but little is known about how these microtubules are organized. Here we identify the spectraplakin, Short stop (Shot), as the cortical anchor for noncentrosomal microtubule organizing centers (ncMTOCs) in the Drosophila oocyte. Shot interacts with the cortex through its actin-binding domain and recruits the microtubule minus-end-binding protein, Patronin, to form cortical ncMTOCs. Shot/Patronin foci do not co-localize with ?-tubulin, suggesting that they do not nucleate new microtubules. Instead, they capture and stabilize existing microtubule minus ends, which then template new microtubule growth. Shot/Patronin foci are excluded from the oocyte posterior by the Par-1 polarity kinase to generate the polarized microtubule network that localizes axis determinants. Both proteins also accumulate apically in epithelial cells, where they are required for the formation of apical-basal microtubule arrays. Thus, Shot/Patronin ncMTOCs may provide a general mechanism for organizing noncentrosomal microtubules in differentiated cells.